Study on Vanadium Recovery from Spent Catalyst Used in the Manufacture of Sulfuric Acid - M. Mousa, Khalid; K. Kouba, Safa (Iraqi Journal of Chemical and Petroleum Engineering, 2010)
Spent catalysts for sulfuric acid production have large amount of vanadium and due to environmental authority it is required to reduce the vanadium contain of the spent catalyst. Experimental investigation was conducted to study the vanadium recovery from spent catalyst via leaching process using sodium hydroxide to study the effect of process variables (temperatures, sodium hydroxide molarities, leaching time and particle size) on vanadium recovery. The effect of process variables (temperature, particle size,molarities of sodium hydroxide and leaching time) on the percentages of vanadium recovery were investigated and discussed .It was found that the percentage of vanadium recovery increased with increasing temperature up to 100 , increasing sodium hydroxide molarity from 2 to 4M, increasing leaching time, decreasing particle size from mesh 150, 100 and 65. A complete vanadium recovery was achieved at the following conditions: temperature (100˚c), particle size (150 mesh ) molarity of Na OH(4 molar) and leaching time(5 h).